Concept and Characteristics of Educational Innovation - Nisa Novia (Social Studies Conference Proceedings, 2021)
The current pace of development requires us always to follow these developments to avoid falling behind, especially in education. Our country is experiencing a decline in education; that is what we feel these days. Because of this, we have to make a change through educational innovation. This article's purpose is to describe the concepts and characteristics of educational innovation. This article was written using library research using data sources from books as references and scientific journal articles. Educational innovation is an effort to make a change to get better things in the field of education. Educational innovation in its implementation has principles and goals. Educational innovation as an effort to change education also cannot stand alone. Still, it must involve all aspects, like the innovators, implementation of innovation involving teachers and students, curriculum, and facilities. Characteristics in educational innovation are traits or characteristics that arise from individual habits that lead to development in the world of education that are supported by ideas, how to think and perceived by the individual or a group that used to solve a problem and achieve goals in the world of education.